Combating white spot lesions via incorporation of remineralizing/ antibacterial additives into orthodontic adhesives: A review - Mohammed, Dana R; Ibrahim, Ali I; Deb, Sanjukta (Journal of Baghdad College of Dentistry, 2025)
Background: Orthodontic treatment with fixed appliances is frequently associated with difficulties in maintaining good oral hygiene and creation of plaque-retentive areas on tooth surfaces that are typically more prone to the development of caries; such drawbacks may result in white spot lesion (WSL) development that affects the esthetic outcome following bracket debonding. This review article focuses on orthodontic WSLs development, prevention, and remineralization potential via incorporating various remineralizing / antibacterial additives into orthodontic adhesives. Results: Unbalanced enamel demineralization and remineralization processes, along with rapid alterations in the dental plaque bacterial ecology, particularly acidogenic bacteria, are the causes of the start and progression of a carious lesion. Without significantly compromising an adhesive mechanical performance, several antibacterial and remineralizing substances have been added to orthodontic adhesives in an effort to reduce bacterial colonization and promote remineralization. Conclusions: Antibacterial and/or remineralizing substances were utilized as additives in the creation of innovative orthodontic adhesive systems to address white spot lesions (WSLs) and improve the ability of enamel remineralization. Compared to adding only one agent, including multiple agents in an orthodontic adhesive system may have a greater impact on lowering enamel demineralization and improving enamel remineralization during orthodontic therapy.